Functional analysis of a novel de novo SCN2A variant in a patient with seizures refractory to oxcarbazepine - Hu, Xiaoyue; Jing, Miao; Wang, Yanping; Liu, Yanshan; Hua, Ying (Frontiers in Molecular Neuroscience, 2023)
Objective: We admitted a female patient with infantile onset epilepsy (<3-month-old). The use of oxcarbazepine exacerbated epileptic seizures in the patient. In the present study, we aimed to identify the genetic basis of the infantile onset epilepsy in the patient, and determine the correlations among genotype, phenotype, and clinical drug response. Methods: We described the clinical characteristics of an infant with refractory epilepsy. Whole exome sequencing (WES) was used to screen for the pathogenic variant. Whole-cell patch-clamp was performed to determine functional outcomes of the variant. Results: WES identified a novel de novo SCN2A variant (c.468 G>C, p.K156N) in the patient. In comparison with wildtype, electrophysiology revealed that SCN2A-K156N variant in transfected cells demonstrated reduced sodium current density, delayed activation and accelerated inactivation process of Na+ channel, all of which suggested a loss-of-function (LOF) of Nav1.2 channel. Conclusion: We showed the importance of functional analysis for a SCN2A variant with unknown significance to determine pathogenicity, drug reactions, and genotype-phenotype correlations. For patients suffering from early infantile epilepsies, the use of oxcarbazepine in some SCN2A-related epilepsies requires vigilance to assess the possibility of epilepsy worsening.